Types and Meanings of Adjuncts in Short Story a Tale of Two Jackets - Arsyada Nihayati; Pradita Lina Dewi Afifah; Afgrill Syaiqilla Putra (UICELL, 2020)
This study is particularly pointed at distinguishing the shapes of aides and the implications they carry. In arrange to analyze the information, the descriptive-qualitative approach was connected in this inquire. The data are sentenced, which contain adverbials working as aides, and they were taken from a brief story entitled A Story of Two Jackets, published by Really Learn English (2016). They were collected through library research and, after that, displayed casually by giving a few cases and elaboration. There are a few essential focuses that can be concluded based on the result of the analysis. First, adjuncts may appear in several sentences. The adjunct phrases found in this short story are adverb phrases and prepositional phrases. Second, the researcher found that there are different meanings of the adjuncts found in the short story. Adjuncts that denote the process have the purpose of the manner. Adjuncts that mean the process have the purpose of the manner. Adjuncts of time have a sense of time position. Adjuncts that indicate space or location has the meaning of position and distance.